2011
DOI: 10.1002/mnfr.201100542
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of protein fermentation to gut health

Abstract: It is generally accepted that carbohydrate fermentation results in beneficial effects for the host because of the generation of short chain fatty acids, whereas protein fermentation is considered detrimental for the host's health. Protein fermentation mainly occurs in the distal colon, when carbohydrates get depleted and results in the production of potentially toxic metabolites such as ammonia, amines, phenols and sulfides. However, the effectivity of these metabolites has been established mainly in in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
381
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 515 publications
(390 citation statements)
references
References 100 publications
2
381
2
5
Order By: Relevance
“…Previous findings have also shown that gene expression of cytokines in the colon increased with high-CP diets, irrespective of dietary fermentable carbohydrate inclusion (17) . This is, to a certain extent, in contrast to our initial hypothesis; however, it can be concluded that in the present study, the decreased expression of MCT1 coincided with increased luminal availability of protein fermentation products such as NH 3 , and the concomitantly increased pro-inflammatory cytokine expression in the colonic mucosa. The role of MCT1 in the transport of butyrate into colonocytes has been well studied.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Previous findings have also shown that gene expression of cytokines in the colon increased with high-CP diets, irrespective of dietary fermentable carbohydrate inclusion (17) . This is, to a certain extent, in contrast to our initial hypothesis; however, it can be concluded that in the present study, the decreased expression of MCT1 coincided with increased luminal availability of protein fermentation products such as NH 3 , and the concomitantly increased pro-inflammatory cytokine expression in the colonic mucosa. The role of MCT1 in the transport of butyrate into colonocytes has been well studied.…”
Section: Discussioncontrasting
confidence: 99%
“…Dietary and endogenous proteins that enter the large intestine of humans or monogastric animal species can be fermented by indigenous bacteria to form metabolites such as NH 3 , hydrogen sulphide, branched-chain fatty acids, phenols and indols, which may promote intestinal disorders (1 -4) . For example, protein level and quality in pig diets have been shown to be related to diarrhoea and shedding of enterotoxigenic Escherichia coli after a challenge (5,6) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As determined in humans by Scott et al (2012), heat-damaged pea protein is less digestible by host enzymes in the small intestine and is therefore reaching the more distal parts of the GIT where protein fermentation dominates. In conclusion, the amount and composition of fermentation metabolites in the different sites of the GIT, mainly in the large intestine, depend on the digestibility of the dietary proteins, which in turn is influenced by the quality, source and level of dietary protein (Windey et al, 2012). Thus, in the following, dietary strategies will be described, aiming to reduce protein fermentation through reduction of growth and metabolic activities of potential protein-fermenting pathogens.…”
Section: Impact Of Dietary Protein On the Incidence Of Pwdmentioning
confidence: 99%
“…Fermentation of the excess of proteins in the gut yields metabolites such as NH 3 and H 2 S, compounds known to be toxic to the mucosa (Corpet et al, 1995). However, human epidemiologic studies do not support an association between protein intake and CRC (Windey et al, 2012).…”
Section: Excess Of Protein and Fat Intakementioning
confidence: 99%